ANALISIS KANDUNGAN VITAMIN C, MUTU ORGANOLEPTIK, MUTU FISIK DAN KIMIA MARMALADE BUNGA ROSELLA MERAH (Hibiscus Sabdariffa, Linn) PADA KONSENTRASI GULA BERVARIASI - Olga Lieke Paruntu; Danirza Nanda Ranti (POLTEKKES KEMENKES MANADO, 2015)
Background :Rosella than as ornamental flowers have benefits for human health , because thecontent of vitamin contained therein. Currently , rosella used as herbs and can be processed intofood , one of which in the form of marmalade. To obtain a marmalade rosella quality both in terms ofvitamins, quality, organoleptic (taste, color, texture and flavor), physical quality ( viscosity and totalsolids ) and chemical quality ( moisture content and pH ) it is necessary to increase the sugarcomposition right .Research Purpose :To determine the level of joy and good quality marmalade red rosella flower withvarying sugar concentrations ( 7.5 % , 10 % , 12.5 % ) .Types of research:This type of research is a quasi experimental study with factorial design . Thedraft for the research carried out 3 times a treatment that 7.5 % of samples ( X1 ) , 10 % ( X2 ) , 12.5% ( X3 ) marmalade red rosella flower is seen in terms of water content, viscosity, total solids and pH. Organoleptic assessment includes an assessment of flavor, color, texture and flavor using ahedonic scale. And then performed the data analysis by t-test .Research result:The content of vitamin C marmalade red rosella flower with a sugar concentration of7.5 % ( X1) is 35.38 mg , 10 % sugar concentration ( X2 ) is 9.94 mg and 12.5 % sugar concentration( X3 ) is 9.68 mg , Good chemical quality of the water content of 46.2 % and a pH of 3.2 to 12.5 %sugar concentration ( X3 ) . Good physical quality CP viscosity of 0.59 and a total solidsconcentration of 59 % to 12.5 % sugar ( X3 ) . Organoleptic quality in terms of both taste and color ofthe sugar concentration of 12.5 % ( X3 ) in terms of texture and flavor sugar concentration of 7.5 %(X1 )